When Piety is Framed as Threatening: The Hijrah Movement within the Politics of Religious Moderation in Indonesia - Hamzah Fansuri (Muslim Politics Review, 2025)
This article investigates how the hijrah movement in Indonesia – characterized by a return to Islamic pious practices, lifestyle changes, and global Muslim identity – is increasingly constructed as a security threat within Indonesia’s religious moderation agenda. Drawing on discourse analysis of state narratives, media portrayals, field research, and statements from mainstream Islamic organizations, the study finds that hijrah is framed not merely as a cultural or spiritual trend but as a potential conduit for ideological deviation and radicalization. Focusing on local responses in urban centers such as Jakarta and Bandung, it examines how the movement and its participants are positioned against state-sanctioned visions of moderate Islam. Using securitization theory and grounded Foucauldian analysis, the article argues that the state's discursive alignment of hijrah with extremism enables soft repression and delegitimization of non-violent yet non-conforming Islamic expressions. This securitizing logic risks narrowing Indonesia’s religious pluralism by stigmatizing identity-based piety, thereby undermining the very goals of tolerance and harmony that moderation policies claim to promote.